Education, information, and improved health: evidence from breast cancer screening - Keith Chen; Fabian Lange (Institute for the Study of Labor (IZA), 2008)
While it is well known that education strongly predicts health, less is known as to why. One reason might be that education improves health-care decision making. In this paper we attempt to disentangle improved decision making from other effects of education, and to quantify how large an impact it has on both a patients demand for health services, and that demands sensitivity to objective risk factors. We do this by estimating a simple structural model of information acquisition and health decisions for data on womens self-reported breast-cancer risk and screening behavior. This allows us to separately identify differences in the ability to process health information and differences in overall demand for health. Our results suggest that the observed education gradient in screening stems from a higher willingness-to-pay for health among the educated, but that the main reason why the educated respond more to risk factors in their screening decision is because they are much better informed about the risk factors they face.
urn:nbn:de:101:1-20080619258
Keywords: I10; 360; Education; allocative efficiency; health; Gesundheitsvorsorge; Informationsverhalten; Frauen; Bildungsniveau; Gesundheit; Krebskrankheit; USA